Application And Impact of Artificial Intelligence in Financial Decision Making - Aparna Krishna Bhat, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
AI in finance refers to the application of AI techniques in financial businesses. With the proliferation of AI-based tools and algorithms in financial decision-making, it is increasingly necessary to assess the impact of these technologies on the investment strategies and results of individual investors. The integration of artificial intelligence (AI) in financial decision-making heralds a technological revolution in the sector, which offers enormous potential benefits and significant challenges. This review aims to unravel the complexity surrounding AI in finance, focusing on identifying and addressing barriers to its effective implementation. Looking ahead, the article anticipates future trends and challenges in AI-driven finance, urging stakeholders to collaborate for sustainable innovation. Overall, AI offers tremendous potential for financial transformation, but careful consideration of ethical and regulatory issues is essential for long-term success.
Keywords: Fraud Detection; Artificial Intelligence; AI Advancements, Machine Learning; Predictive Analytics; Irregularities, Anomalous Patterns, Advanced Algorithms; Fraudulent Behavior; Compliance, Risk Management; Financial Markets; Wealth Management; Asset Management; AI-Driven Tools; Financial Decision-Making; Mixed-Methods Approach; Technology Adoption; Challenges